Effects of ultrafine grinding on physicochemical, functional and surface properties of ginger stem powders. (28th July 2020) - Zhao, Xiaoyan; Meng, Ang; Zhang, Xiaowei; Liu, Hongkai; Guo, Dongju; Zhu, Yunping
Abstract: BACKGROUND: Ginger stem (GS) is a by‐product of ginger processing. It is not directly edible as a feed or food, which leads to it being discarded as waste or burned. Accordingly, it is very important to develop new functional products in the food or feed industry as a result of high nutritional and medicinal values. In the present study, the structures and physicochemical properties of GS powders of different sizes were evaluated after ultrafine grinding by a vibrating mill. RESULTS: The ultrafine powders exhibited a smaller particle size and uniform distribution. Higher values in bulk density (from 1.07 ± 0.06 to 1.62 ± 0.08 g mL −1 ), oil holding capacity (from 3.427 ± 0.04 to 4.83 ± 0.03 g mL −1 ), and repose and slide angles (from 42.33 ± 1.52 to 54.36 ± 1.15° and 33.62 ± 0.75 to 47.27 ± 1.34°, respectively) of ultrafine GS powders were exhibited compared to coarse powders. With a reduced particle size, the solubility of ultrafine powders increased significantly ( P  < 0.05), whereas the water holding and swelling capacities decreased with a reduced particle size and then increased. Fourier transform infrared spectroscopy analysis showed that ultrafine grinding did not damage the main cellular structure of GS powder. The reduction of fiber length and particle size in GS was observed by light microscopy and scanning electron microscopy. The X‐ray diffraction patterns demonstrated the crystallinity and the intensity of the peak in superfine GS powders. CONCLUSION: The present study suggests that ultrafine grinding treatments influence the structures and physicochemical properties of GS powders, and such changes would improve the effective utilization of GS in the food or feed industry. © 2020 Society of Chemical Industry